Immunogenic variants obtained by mutagenesis of mouse mastocytoma P815. II. T lymphocyte-mediated cytolysis (The Rockefeller University Press, 1980)
Tumor cell variants that were rejected by syngeneic mice (tum-) were obtained from mastocytoma P815 by mutagenesis (as described in the accompanying report (13). A considerable T lymphocyte-mediated lysis was observed upon incubation of these tum- variants with peritoneal exudate cells collected a few days after an intraperitoneal challenge of immune animals. Spleen cells from these animals were cytolytic after stimulation in vitro with the immunizing variant. New antigens, absent from the original P815 tum+ cells, were detected on 15 of the 21 tum- variants that were tested. All these antigens appeared to be different. No new antigen was detected on any of 10 mutagenized P815 clones that had retained their ability to form tumors. We compared the evidence obtained in vivo and in vitro for the presence of specific antigens on five tum- variants. Three variants were shown both in vivo and in vitro to carry an individual antigen. One showed no specificity either in vivo or in vitro. However, for one variant, no specificity was observed in vivo, although cytolysis tests demonstrated the existence of a singular antigenic specificity.